Brefeldin A Inhibits Cell-Free, De Novo Synthesis of Poliovirus - Cuconati, Andrea (American Society for Microbiology, 1998)
Brefeldin A (BFA), an inhibitor of intracellular vesicle-dependent secretory transport, is a potent inhibitor of poliovirus RNA replication in infected cells. We have determined that the unknown mechanism of BFA inhibition of replication is reproduced in the cell-free poliovirus translation, replication, and encapsidation system. Furthermore, we provide evidence suggesting that the cellular mechanism targeted by BFA, the GTP-dependent synthesis of secretory transport vesicles, may be involved in viral RNA replication in the system via a soluble cellular GTP-binding and -hydrolyzing activity. This activity is related to the ARF (ADP-ribosylation factor) family of GTP-binding proteins. ARFs are required for the formation of several classes of secretory vesicles, and some family members are indirectly inactivated by BFA. Peptides that function as competitive inhibitors of ARF activity in cell-free transport systems also inhibit poliovirus RNA replication, and this inhibitory effect can be countered by the addition of exogenous ARF. We suggest that BFA inhibition of replication is diagnostic of a requirement for ARF activity in the cell-free system.